2020
DOI: 10.3390/rs12233928
|View full text |Cite
|
Sign up to set email alerts
|

Intelligent Mapping of Urban Forests from High-Resolution Remotely Sensed Imagery Using Object-Based U-Net-DenseNet-Coupled Network

Abstract: The application of deep learning techniques, especially deep convolutional neural networks (DCNNs), in the intelligent mapping of very high spatial resolution (VHSR) remote sensing images has drawn much attention in the remote sensing community. However, the fragmented distribution of urban land use types and the complex structure of urban forests bring about a variety of challenges for urban land use mapping and the extraction of urban forests. Based on the DCNN algorithm, this study proposes a novel object-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 65 publications
(71 reference statements)
0
8
0
Order By: Relevance
“…The authors found that these satellites offer temporal resolution and other characteristics, such as wavelength, were deemed useful for the analysis of urban forest at the landscape scale. However, He et al [87], argue that spectral indices derived from medium resolution imagery are still limited in extensive use in cities since many elements have similar spectral signatures, which cause strong heterogeneity and make object classification difficult.…”
Section: Satellite Imagerymentioning
confidence: 99%
See 2 more Smart Citations
“…The authors found that these satellites offer temporal resolution and other characteristics, such as wavelength, were deemed useful for the analysis of urban forest at the landscape scale. However, He et al [87], argue that spectral indices derived from medium resolution imagery are still limited in extensive use in cities since many elements have similar spectral signatures, which cause strong heterogeneity and make object classification difficult.…”
Section: Satellite Imagerymentioning
confidence: 99%
“…WorldView 3 (WV3), which achieves a higher spatial resolution (2 m) in the spectral bands compared to WV2, was used as the unique data source in two studies [86,87]. Namely, Vahidi et al [86] used WV3 for tree identification in urban orchards obtaining 91% accuracy.…”
Section: Satellite Imagerymentioning
confidence: 99%
See 1 more Smart Citation
“…To solve these boundary problems, the most commonly used method is skip connections, where shallow layers are fused in the CNNs due to the rich contour information [12,31]. Mou et al [32] proposed a method that combined FCN [33] and a recurrent neural network (RNN [34]) for achieving accurate object boundary inference and semantic segmentation [35].…”
Section: Boundary Problemsmentioning
confidence: 99%
“…The extraction methods of urban land use information mainly include support vector machines [7,8], decision trees [9], random forest (RF) models [10,11], and deep learning [12][13][14]. Most of these methods are based on supervised learning, which requires many labeled samples for model training [15].…”
Section: Introductionmentioning
confidence: 99%